Pregabalin Abuse in between Jordanian youths need to concern (International Journal of Scientific Research and Management (IJSRM), 2019)
Pregabalin is a medication used extensively in neurosurgery and mental health care as it is sometimes used in primary health care in medical conditions but is increasingly reported as a potential increase of use leads to misuse and abuse. The fact, increase both levels of abuse and death; along with the growing non-medical use through black market have been reported in Jordan.